OBTAINING AMINES FROM PLASTIC WASTE (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The burgeoning issue of plastic waste has propelled research towards innovative solutions. This article explores the extraction of amines from plastic waste as a sustainable approach, highlighting its potential in mitigating environmental pollution while offering valuable chemical resources. Through a comprehensive literature review and experimental analysis, this study elucidates the methods, results, and implications of amines extraction, underscoring its significance in the realm of green chemistry.